2020
DOI: 10.36347/sjmcr.2020.v08i01.022
|View full text |Cite
|
Sign up to set email alerts
|

Xeroderma Pigmentosum: Exenteration of Palpebral Basocellular Carcinoma

Abstract: Case ReportXeroderma Pigmentosum (XP) is a very rare genetic disease characterized by extreme sensitivity to the sun. We report a case showing a very bad evolution leading to palpebral exenteration in a 21 years old patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…9 In addition, Bouzouba et al showed the impact of intralesional bevacizumab in childhood palpebral hemangioma. 10 Sunitinib malate is a tyrosine kinase inhibitor (TKI), which blocks VEGFR-1/2, platelet-derived growth factor receptors, FMS-like tyrosine kinase III, and receptor tyrosine kinase C-KIT. 11 In-vivo studies reported reduced endothelial cell growth through accumulation in the sub-G1 phase and decreased hemangioma cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…9 In addition, Bouzouba et al showed the impact of intralesional bevacizumab in childhood palpebral hemangioma. 10 Sunitinib malate is a tyrosine kinase inhibitor (TKI), which blocks VEGFR-1/2, platelet-derived growth factor receptors, FMS-like tyrosine kinase III, and receptor tyrosine kinase C-KIT. 11 In-vivo studies reported reduced endothelial cell growth through accumulation in the sub-G1 phase and decreased hemangioma cell migration.…”
Section: Discussionmentioning
confidence: 99%